CROSS-SECTIONAL STUDY ON EQUINE LUNG WORM AND ASSOCIATED RISK FACTOR IN AMBO DISTRICT, OROMIA REGION, ETHIOPOIA - Negasa, Tolesa; Dilbato, Tegegn; Gudeta, Daba (International Journal of Research -GRANTHAALAYAH, 2017)
To determine the prevalence of lungworm, Dictyocacaulus arnifieldi and identify risk factors associated with occurrence of diseases in equines in and around Ambo town, in Oromia region, Ethiopia. Equine lungworm, Dictyocacaulus arnifieldi is a parasitic disease that affects horses, donkeys and mules, is widespread in study area. The infection is transmitted by ingestion of contaminated pasture which contains infective stage larvae of Dictyocacaulus arnifieldi. To-date, effective control program still remains to be a reality and needs to be strengthened. Purposive sampling technique was used to select study animals and performed using modified Berman technique in Ambo University veterinary laboratory technology. Descriptive statistics and logistic regression used to analyze using STATA statistical software version 9. From the total 384 equines (donkeys, n= 313, mules, n= 29, and horses, n= 42) the positive animal was 77 resulting the overall prevalence 20.1% equine lungworm. There is significance difference between Kebele (small admistrative unit), age, body condition and seasons of the study period (p<0.05). The study suggests that the community of the study area was highly affected lungworm infection, Dictyocacaulus arnifieldi. Therefore, awareness should be created to the owners regarding the management system of equine was recommended.